PENINGKATAN MUTU PENDIDIKAN DI MADRASAH IBTIDAIYAH NORRAHMAN KECAMATAN BANJARMASIN SELATAN KOTA BANJARMASIN - Zakiyyah Zakiyyah; Nurul Qomariyah (DARRIS: Jurnal Pendidikan Madrasah Ibtidaiyah, 2018)
This study discusses the "educational enhancement in Norrahman Subdistrict of Bacolod MI South of the town of Banjarmasin". Formulation of the problem in this research is how the educational enhancement in Norrahman Subdistrict of Bacolod MI South of the town of Banjarmasin and what are the factors that influence quality improvement in education in MI Norrahman Kecamatan Banjarmasin South Of The City Of Banjarmasin. Based on the formulation of the problem, then the purpose of this research is to know the educational enhancement in Norrahman Subdistrict of Bacolod MI South of the town of Banjarmasin as well as factors that affect the educational enhancement in MI Norrahman Subdistrict Of Bacolod South Of The City Of Banjarmasin. The subject in this study is the teacher MI Norrahman Subdistrict of Bacolod South of the city of Banjarmasin, while being the object of research is educational enhancement in Norrahman Subdistrict of Bacolod MI South of the town of Banjarmasin and the factors that influence quality improvement in education in Norrahman Subdistrict of Bacolod MI South of the city of Banjarmasin. Data collection techniques used in this research is the observation, interviews, documentation. The data processing is done by editing techniques, data classification, and interpretation of data. While the data analysis techniques using qualitative descriptive analysis by way of describing and outlining any data obtained and to take the conclusions are deductive inferences in a way that is common, leading to the conclusion that is special. Based on the results of the research that has been done, it is noted that the effort to Increase the quality of education in the Norrahman Subdistrict of Bacolod MI South of the town of Banjarmasin has gone well, it is influenced by several factors including factor the teacher, a factor communication between teachers and students, economic factors, and supporting facilities and infrastructure so that the process of improving the quality of education in the Norrahman Subdistrict of Bacolod MI South of the city of Banjarmasin. Key Words: Improved, The Quality Of Education, The Madrasa.